2013
DOI: 10.1002/jbm.a.34939
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of aged human mitral valve leaflets

Abstract: Objective To characterize the mechanical properties of aged human anterior (AML) and posterior (PML) mitral leaflets. Materials and Methods The AML and PML samples from explanted human hearts (n = 21, mean age of 82.62 ± 8.77 years old) were subjected to planar biaxial mechanical tests. The material stiffness, extensibility and degree of anisotropy of the leaflet samples were quantified. The microstructure of the samples was assessed through histology. Results Both the AML and PML samples exhibited a nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 74 publications
(134 reference statements)
3
37
0
Order By: Relevance
“…Fortunately, in the past decade, the mechanical testing techniques and constitutive modeling in cardiovascular mechanics have improved tremendously. Human tissue material properties can now be tested extensively (Pham and Sun, 2013), modeled and implemented in computational studies (Wang and Sun, 2013). Improved computational models of MV has evolved (Krishnamurthy et al, 2009; Kunzelman et al, 1993; Pouch et al, 2012; Prot et al, 2009; Stevanella et al, 2011; Weinberg and Kaazempur Mofrad, 2007) and predicted several diseased states (Kunzelman et al, 1997; Prot et al, 2010; Wenk et al, 2010; Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, in the past decade, the mechanical testing techniques and constitutive modeling in cardiovascular mechanics have improved tremendously. Human tissue material properties can now be tested extensively (Pham and Sun, 2013), modeled and implemented in computational studies (Wang and Sun, 2013). Improved computational models of MV has evolved (Krishnamurthy et al, 2009; Kunzelman et al, 1993; Pouch et al, 2012; Prot et al, 2009; Stevanella et al, 2011; Weinberg and Kaazempur Mofrad, 2007) and predicted several diseased states (Kunzelman et al, 1997; Prot et al, 2010; Wenk et al, 2010; Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…79 A study from patients aged 72–91 years without cardiac disease confirmed the well‐known calcification concentrated along the annulus or chordal insertion regions, but remarkably minimal changes in leaflet mechanical properties. 80 Unlike the semilunar cardiac valves, age‐dependent biological changes in the mitral valve are not well understood.…”
Section: Mitral Valve Ageingmentioning
confidence: 99%
“…For the PML, the average thickness values of the leaflet belly and edge were 1.31 mm and 1.57 mm respectively. The leaflet belly and edge regions were identified as previously described 24 .…”
Section: Patient and Methodsmentioning
confidence: 99%
“…The material properties of the MV apparatus were obtained from an age- and gender-matched cadaver heart, i.e., 69 year old patient, from our previously published studies of human MV leaflets 24 and chordae tendineae 27 material characterization. Figure 2 shows the stress-strain curves from an equibiaxial protocol of the AML and PML leaflets in both directions and of four chords (AB was assumed to be equivalent to PB).…”
Section: Patient and Methodsmentioning
confidence: 99%